نظام التكاليف على أساس الأنشطة الموجهة بالوقت (tdabc) وأثره على الربح، دراسة تطبيقية على الشركات السعودية - علي فايع محمد ال حسن (My University, 2017)
هدفت هذه الدراسة للتعرف على مدى تطبيق الشركات السعودية لنظام التكاليف على أساس الأنشطة الموجهة بالوقت (TDABC) وأثر ذلك في تخفيض التكاليف. وبينت نتائج البحث وجود أثر معنوي لنموذج الانحدار لتطبيق الشركات السعودية لنظام (TDABC) في تخفيض التكاليف بالشركات السعودية، وهو تأكيد على وجود فاعلية وأثر لتطبيق الشركات السعودية لنظام (TDABC) في تخفيض التكاليف بالشركات السعودية، بالإضافة إلى إن إجمالي ما يؤثر به تطبيق الشركات لنظام (TDABC) في تخفيض التكاليف بالشركات السعودية من عوامل يبلغ (68.6%) وأن ما تبقى من الأثر والذي يبلغ (31.4%) يعزوه الباحث إلى عوامل ومتغيرات خارج نطاق الدراسة. Abstract: The objective of this study was to identify the extent which Saudi companies applied Time-driven Activity-based Costing (TDABC) and the impact of this on reducing costs. The results of the research showed that there is a significant effect of the regression model for the application of Saudi companies Time-driven Activity-based Costing (TDABC) and the impact of this on reducing costs, which a confirmation of the existence of the effectiveness and impact of the application of Saudi Companies system (TDABC) in reducing costs Saudi Companies; The total factors affecting the application of Saudi companies to the (TDABC) is equal(68.6%) and (31.4%) are other factors.
Keywords: نظام التكاليف، الأنشطة الموجهة بالوقت، الشركات السعودية، الربح، تخفيض التكاليف